Practices and beliefs about exclusive breastfeeding by women living in Commune 5 in Cali, Colombia (Colombia Medica, 2010)
Objective: To describe the practices and beliefs about breastfeeding during the first 6 months after delivery, a study was completed with women living in Commune 5 in Cali, Colombia. Methods: The methodology used for the study was ethno nursing, which facilitated inquiring about the emic perspective and identifying beneficial and risk-laden practices for the child´s health regarding feeding. Fifteen women were the key informants; this sample was determined by data saturation criteria. Findings: Findings are presented in two parts: practices and beliefs in favor of exclusive breastfeeding and practices and beliefs that do not support exclusive breastfeeding. The prominent practices and beliefs in favor of exclusive breastfeeding are related to the mother´s bond with the child, preparation for breastfeeding during pregnancy, and family support. Among the practices and beliefs not supporting maternal breastfeeding, we must highlight the mother´s lack of confidence in her breast milk production. Conclusions: Knowledge generated by this study may facilitate nursing care of women during pregnancy and postpartum that is congruent with their culture. To accomplish this, we identified cultural practices that should be kept and others needing modification or restructuring.